Trichoderma koningii as a biomineralizing fungous agent of calcium oxalate crystals in typical Argiudolls of the Los Padres Lake natural reserve (Buenos Aires, Argentina) - Oyarbide, Fabricio (2001)
The aim of the present study, performed on typical Argiudolls in a natural reserve with little or no anthropic impact, was to characterize the fungous biomineralizing process of calcium oxalate crystals in organic horizons of the soil. The chosen sites possessed different plant cover, identified as acacia woods and grassy meadows with particular micro environmental conditions that have differing effects in the process of biomineralization. The contribution of the plant material in the soil is a key factor since 1) it generates the particular composition of the organic horizons, 2) it determines the nature of decomposing organisms, and 3) it affects the presence, composition and development of biominerals. According to the results obtained, the acacia woods prove to be a site comparatively more favorable to the fungous biomineralizing process. This makes itself manifest in the greater abundance and development of crystals in the organic horizons of the soil, resulting in whewellite (CaC2O4 · H2O) and weddellite (CaC2O4 · (2 + x) H2O) regarding biomineral species developed, the latter being the major component. The observation of both species of biominerals is noteworthy since it represents the first cited in the country. The isolated fungous organisms were Trichoderma koningii, and Absidia corymbifera. T. koningii was identified as the most active biomineralizing organism thus constituting the first reference to indicate this species as a biomineral producing agent.